(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
The article on carbon nanotube production technology and their practical use (carbon nanotube production technology), author Uktam Dekhkonovich Sherkulov, Navoi State Pedagogical Institute. The article provides information on the technologies for obtaining nanotubes. The main 8 technologies are described in detail. The article is intended for scientific researchers and graduate students. The article is intended for graduate students and scientific researchers.